Is There A Post Listing Anomaly For IPOs Overseas Listing? - FADL, Moustafa (Asian Journal of Empirical Research, 2013)
Both the IPO literature and cross listing literature document that soon after the overseas listing of IPOs, the results are negative abnormal returns, and that phenomenon are “ post listing anomaly”. This paper checks whether there is a post listing anomaly and tries to find reasons for it. The paper concludes that the post listing anomaly does not exist. Further, some companies time the market while others do not when they consider listing their IPOs overseas.